Penanganan Hipotiroid pada Anak dengan Sindrom Nefrotik - Bernadetha Nadeak (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2020)
Hypothyroid or thyroid hormone deficiency is a state of hormone deficiency due to the thyroid gland not being able to produce sufficient amounts. This hypothyroid is a complication that often occurs in nephrotic syndrome, but often does not show clinical symptoms. Hypothyroid in nephrotic syndrome occurs due to the release of thyroid hormone and thyroxin-binding globulin (TBG) through urine which will reduce the concentration of free thyroid hormone and increase thyroid stimulating hormone (TSH). The purpose of writing this article is to find out how to manage hypothyroid in children with nephrotic syndrome. The method used in this paper is qualitative research with a "library research" approach, where researchers as "key instruments" read theories that are directly related to the topic of writing sourced from books, journals, proceedings and other documents (online and printed) and make it into research data which were analyzed descriptively. The results of this study suggest that the condition of hypothyroid in patients with nephrotic syndrome often does not show typical clinical symptoms. So suggestions for screening for thyroid function need to be considered. Thus it is known quickly if there is a hypothyroid condition and its possible complications, and can be normalized thyroid hormone concentration (FT 3, FT 4, TSH) by using TSH as a marker of succession replacement therapy. The conclusion is hypothyroid is a complication that can occur in nephrotic syndrome which can cause complications in the form of growth and development disorders and can increase the risk of death or mortality, so that management must be carried out which, thereby reducing mortality or mortality Keywords : child, hypothyroid, nephrotic syndrome